2021
DOI: 10.3389/fmed.2021.699880
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Accuracy of National Early Warning Score 2 on Predicting Clinical Deterioration for Patients With COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: During the coronavirus disease 2019 (COVID-19) pandemic, the National Early Warning Score 2 (NEWS2) is recommended for the risk stratification of COVID-19 patients, but little is known about its ability to detect severe cases. Therefore, our purpose is to assess the prognostic accuracy of NEWS2 on predicting clinical deterioration for patients with COVID-19.Methods: We searched PubMed, Embase, Scopus, and the Cochrane Library from December 2019 to March 2021. Clinical deterioration was defined as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
2
20
1
1
Order By: Relevance
“…Our prospective study resolves these shortcomings as it was conducted on a larger sample size, thus reducing the chances of error and allowing more accurate prediction. In the pre-COVID period, a score of 5 to 6 indicated a medium risk of deterioration, while a score of 7 or more indicated a high risk of deterioration as per Royal College of Physicians standards [20]. However, in our study on COVID-19 patients, we found that a NEWS2 cut-off score ≥ 6 on admission had higher risk of mortality.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…Our prospective study resolves these shortcomings as it was conducted on a larger sample size, thus reducing the chances of error and allowing more accurate prediction. In the pre-COVID period, a score of 5 to 6 indicated a medium risk of deterioration, while a score of 7 or more indicated a high risk of deterioration as per Royal College of Physicians standards [20]. However, in our study on COVID-19 patients, we found that a NEWS2 cut-off score ≥ 6 on admission had higher risk of mortality.…”
Section: Discussioncontrasting
confidence: 48%
“…The role of NEWS2 in COVID- 19 has not yet been thoroughly investigated, even though it is commonly used in clinical practice. According to the advice of Royal College of Physicians, NEWS2 should be utilized while monitoring COVID-19 patients, although, further evaluation should be made if there is any rise in oxygen requirements [20]. Using NEWS2 will make sure that patients who are worsening or at risk of deterioration are recognized and examined as soon as possible by a qualified clinical decision maker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations